2017
DOI: 10.1007/s00787-017-1020-0
|View full text |Cite
|
Sign up to set email alerts
|

Medical comorbidities in children and adolescents with autism spectrum disorders and attention deficit hyperactivity disorders: a systematic review

Abstract: Somatic disorders occur more often in adult psychiatric patients than in the general adult population. However, in child and adolescent psychiatry this association is unclear, mainly due to a lack of integration of existing data. To address this issue, we here present a systematic review on medical comorbidity in the two major developmental disorders autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD) and formulate clinical recommendations. The literature was searched using the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
131
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(152 citation statements)
references
References 60 publications
7
131
1
4
Order By: Relevance
“…Widespread interest in medical comorbidities began in the mid-1990s, and over the past 20 years, studies have indicated that many if not most individuals on the autism spectrum suffer from one or more medical problems (Muskens et al, 2017).…”
Section: Medical Comorbiditiesmentioning
confidence: 99%
“…Widespread interest in medical comorbidities began in the mid-1990s, and over the past 20 years, studies have indicated that many if not most individuals on the autism spectrum suffer from one or more medical problems (Muskens et al, 2017).…”
Section: Medical Comorbiditiesmentioning
confidence: 99%
“…Across the lifespan, autistic individuals have a higher probability than people in the general population to have other health conditions (Davignon et al, 2018, Kohane et al, 2012, Muskens et al, 2017, Soke et al, 2018, Weiss et al, 2018, likely due to shared biological causes and/or the experiences of living with autism (Lai et al, 2014, Vorstman et al, 2017. Common co-occurring neurodevelopmental challenges include intellectual disability, attention-deficit/hyperactivity disorder (ADHD), tic disorders, learning disorders (Lundstrom et al, 2015) and genetic anomalies (Richards et al, 2015, Vorstman et al, 2017.…”
Section: Treating Co-occurring Health Conditionsmentioning
confidence: 99%
“…Common co-occurring neurodevelopmental challenges include intellectual disability, attention-deficit/hyperactivity disorder (ADHD), tic disorders, learning disorders (Lundstrom et al, 2015) and genetic anomalies (Richards et al, 2015, Vorstman et al, 2017. Most common physical conditions include epilepsy (Bolton et al, 2011, Jokiranta et al, 2014, immunological disorders (eg, atopy), gastrointestinal (eg, OSF preprint first posted online July 19, 2018; https://dx.doi.org/10.31219/osf.io/8z5rvThe copyright holders for this preprint (which was not peer-reviewed) are the authors constipation) and sleep problems (Bauman, 2010, Croen et al, 2015, Jones et al, 2016, Kohane et al, 2012, Muskens et al, 2017. Most common mental health issues include anxiety, irritability, self-injurious behaviour, obsessive-compulsive disorder, mood disorders (including depression), suicidal risk, eating disorders, and psychotic disorders (Howes et al, 2018, Lai et al, 2014.…”
mentioning
confidence: 99%
“…As a result, children with ASD are treated with polypharmacy regimens often off-label. ASD and Attention Deficit Hyperactivity Disorder (ADHD) co-occurrence, formally recognized only in the latest version of the Diagnostic and Statistical Manual of Mental Disorders (DSM-V), has presented clinicians with challenges in terms of effective treatments (10). _________________________________________ Pharmacists are in a unique position to help caregivers of ASD children in counselling regarding the use of prescription and over-the-counter medications, particularly in the complexity of attempting to control a myriad of symptoms.…”
Section: Introductionmentioning
confidence: 99%